2018
DOI: 10.3126/ajms.v9i1.17347
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of treadmill exercise on metabolic, physiological and hemodynamic functions of apparently healthy individuals.

Abstract: Background: According to the World Health Organization (WHO), 60 to 85% of the population worldwide does not engage in enough activity; making physical inactivity the fourth leading risk factor for global mortality. Aims and Objectives: This study evaluated the effect of treadmill exercise on liver enzymes, lipid profile, glucose, albumin, blood pressure and pulse rate of apparently healthy students of Nigerian Law School, Enugu Campus, Enugu State Nigeria. Materials and Methods: Sixty (60) students (30 males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As reported by Billah et al [6], fasting blood glucose was determined by Glucose Oxidase-Peroxidase method [18], cholesterol was determined by Cholesterol Oxidase-Peroxidase method [19], triglycerides was determined by the method of Glycerol Phosphate Oxidase-Peroxidase [20], high density lipoprotein cholesterol was determined by Poly ethylene glycol [PEG] precipitation method [21], and low density lipoprotein cholesterol was determined by the method of Assman et al [22] as reported by Ojiako et al [23]. Serum electrolytes were analyzed in the hospital using a Sensacore Electrolyte Analyser made in India, and properly followed the manufacturer's operational protocol.…”
Section: Measurement Of Biochemical Parametersmentioning
confidence: 99%
“…As reported by Billah et al [6], fasting blood glucose was determined by Glucose Oxidase-Peroxidase method [18], cholesterol was determined by Cholesterol Oxidase-Peroxidase method [19], triglycerides was determined by the method of Glycerol Phosphate Oxidase-Peroxidase [20], high density lipoprotein cholesterol was determined by Poly ethylene glycol [PEG] precipitation method [21], and low density lipoprotein cholesterol was determined by the method of Assman et al [22] as reported by Ojiako et al [23]. Serum electrolytes were analyzed in the hospital using a Sensacore Electrolyte Analyser made in India, and properly followed the manufacturer's operational protocol.…”
Section: Measurement Of Biochemical Parametersmentioning
confidence: 99%